Nursing Care of Patients With Cirrhosis: The LiverHope Nursing Project. Issue 3 (22nd March 2020) - Fabrellas, Núria; Carol, Marta; Palacio, Ester; Aban, Marites; Lanzillotti, Tommaso; Nicolao, Gea; Chiappa, Maria Teresa; Esnault, Vanessa; Graf‐Dirmeier, Sabine; Helder, Jeltje; Gossard, Andrea; Lopez, Mireia; et al.
Abstract : Cirrhosis is a complex disease that is associated with disturbances in different organs besides the liver, including kidneys, heart, arterial circulation, lungs, gut, and brain. As a consequence, patients develop a number of complications that result in frequent hospital admissions and high morbidity and mortality. Patients with cirrhosis require constant and rigorous monitoring both in and outside the hospital. In this context, the role of nurses in the care of patients with cirrhosis has not been sufficiently emphasized and there is very limited information about nursing care of patients with cirrhosis compared with other chronic diseases. The current article provides a review of nursing care for the different complications of patients with cirrhosis. Nurses with specific knowledge on liver diseases should be incorporated into multidisciplinary teams managing patients with cirrhosis, both inpatient and outpatient. Conclusion: Nurses play an important role in the management and prevention of complications of the disease and improvement in patients' quality of life and bridge the gap between clinicians and families, between primary care and hospital care, and provide medical education to patients and caregivers.